2017
DOI: 10.1007/s00330-017-5087-2
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic neurosteatosis: Relationship with age, gender, obesity and height

Abstract: • MR proton density fat fraction is highly reproducible at multiple levels. • Sciatic intraneural fat is positively correlated with increasing age (p < 0.05). • Positive correlations exist between bilateral sciatic nerve areas and age (p < 0.05). • Males had significantly higher sciatic intraneural fat than females (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
4
8
1
Order By: Relevance
“…Although not clearly demonstrated by previous study, a potential relationship between obesity and the FF and CSA of peripheral nerves has been suggested. 25,34 Our statistical comparison of BMI between the patient and volunteer groups revealed no signi cant difference in our study.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Although not clearly demonstrated by previous study, a potential relationship between obesity and the FF and CSA of peripheral nerves has been suggested. 25,34 Our statistical comparison of BMI between the patient and volunteer groups revealed no signi cant difference in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…Previous studies have suggested that age and sex have a signi cant relationship with nerve FF and CSA. 15,25 Our study used data from age-and sex-matched case-control subjects, which means that our results are free from that concern. Although not clearly demonstrated by previous study, a potential relationship between obesity and the FF and CSA of peripheral nerves has been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analyses might allow distinguishing between healthy nerve and diseased nerve, and peripheral neuropathy type as it has been shown by others ( 5 , 7 11 ). Additionally, our segmentation could serve as a volume of interest for other quantitative MR methods like diffusion-weighted imaging, magnetization transfer imaging, and relaxometry ( 3 8 , 10 ), which might further be applied to assess total lesion burden, distribution pattern of lesions, and multi-model characterization of lesions. However, such potential outcome measures will only find acceptance in a clinical setting, if they can be obtained in an accurate and time-efficient manner without tedious and labor-intensive manual segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, asymptomatic muscle atrophy and fatty infiltration are seen with aging, not to be confused with chronic denervation. 18 Nerves can be bifid and can demonstrate an intramuscular course as a normal variant. 19 From a functional standpoint, peripheral nerves are divided into sensory, motor, and mixed nerves.…”
Section: Tip 1: Acquire a Good Knowledge Of Neuromuscular Anatomymentioning
confidence: 99%